2002
DOI: 10.1046/j.1468-1331.2002.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal subarachnoid hemorrhage in Baltic population: experience from Latvia (1996–2000)

Abstract: Better knowledge of clinical epidemiology and course of aneurysmal subarachnoid hemorrhage (ASAH) is essential for dedicated planning of the need for services. The aim of the study was to obtain a picture of epidemiology and clinical course of ASAH in Riga City (the capital of Latvia). A retrospective population-based study included residents of Riga City who suffered their first ASAH during a 5-year period from the beginning of 1996 till the end of 2000. The total number of ASAH events in the population durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
3
1
Order By: Relevance
“…In Germany, we identified a mean CFR of aSAH of 15.9%. This is lower than in the UK study (ranging between 29.1% and 37.1%), and in a study from the city of Riga (45%) [23, 28]. In contrast to the meta‐analysis and to the UK study, which both described decreases in CFR over time, in Germany, aSAH‐associated CFR remained stable throughout the entire study period.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In Germany, we identified a mean CFR of aSAH of 15.9%. This is lower than in the UK study (ranging between 29.1% and 37.1%), and in a study from the city of Riga (45%) [23, 28]. In contrast to the meta‐analysis and to the UK study, which both described decreases in CFR over time, in Germany, aSAH‐associated CFR remained stable throughout the entire study period.…”
Section: Discussioncontrasting
confidence: 68%
“…This may also explain parts of the observed differences in trends in case fatality rates (CFRs) between Germany and other regions. In Germany, we of Riga (45%) [23,28]. In contrast to the meta-analysis and to the UK study, which both described decreases in CFR over time, in Germany, aSAH-associated CFR remained stable throughout the entire study period.…”
Section: Discussionmentioning
confidence: 79%
“…Exclusion of 2 studies 12,14 which did not report 1-month outcomes, and 1 study with an exceptionally low case-fatality rate of 8%, 39 did not substantially alter the results. Eighteen studies including our own 11,13,[21][22][23][24][25][27][28][29][31][32][33]35,37,38 reported the mean age of cases with SAH and proportion of women. After adjustment for age and sex, there was a similar but nonsignificant reduction in case-fatality of 0.9% per annum (Ϫ0.2 to 2.0%, p ϭ 0.10).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…1 Overall mortality for SAH is still more than 30%, and morbidity is also significant. [2][3][4] Although SAH comprises less than 10% of cases of cerebrovascular disease, its high associated mortality and morbidity make SAH an important public health threat, and identifying risk factors for SAH is important for its prevention. 5 Risk factors for SAH have been investigated in numerous epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%